WORK AWARDS: CONCEPTS AND POLICIES FOR NON-PNS LECTURERS AT PTKIN - Risnita -; Sohiron - (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2022)
Job appreciation is an important study in human resource management (HRM). Job rewards are a motivating strategy to mobilize HR in achieving organizational goals. Work awards are the total rewards received by employees for their contributions to the organization. The types of rewards that organizations can give to employees are intrinsic rewards (sourced from employees) and extrinsic rewards (sourced from the organization). The award must meet six factors which include: (1). Availability (Availability); (2). Appropriateness (timeliness); (3). Relating to performance (performance contingency; (4). Durability); (5). Fairness (equity); and (6). Clear (visibility). The work award policy for Non-PNS lecturers at PTKIN is clearly stated in the rights of non-civil servant lecturers Regulation of the Minister of Religion Number 3 of 2016 concerning Appointment of Permanent Lecturers who are not Civil Servants of State Religious Universities. Abstrak: Penghargaan kerja merupakan kajian penting dalam manajemen sumber daya manusia (MSDM). Penghargaan kerja merupakan strategi memotivasi untuk menggerakan SDM dalam mencapai tujuan organisasi. Penghargaan kerja merupakan keseluruhan imbalan yang diterima oleh pegawai atas kontribusi yang diberikannya kepada organisasi. Adapun jenis penghargaan yang dapat diberikan organisasi kepada pegawai berupa penghargaan intrinsik (bersumber dari pegawai) dan ekstrinsik (bersumber dari organisasi). Pengahargaan harus memenuhi enam faktor yang meliputi: (1). Ketersediaan (Availability); (2). Kepantasan (timeliness); (3). Berhubungan dengan kinerja (performance contingency; (4). Tahan lama (durability); (5). Keadilan (equity); dan (6). Jelas (visibility). Kebijakan penghargaan kerja bagi dosen Non PNS di PTKIN tertuang secara jelas di dalam hak dosen Non PNS Peraturan Menteri Agama Nomor 3 Tahun 2016 tentang Pengangkatan Dosen Tetap Bukan Pegawai Negeri Sipil Perguruan Tinggi Keagamaan Negeri. Kata-kata kunci: konsep penghargaan kerja, kebijakan, dosen non PNS